Adaptive Behavior, Emotional/Behavioral Problems and Parental Stress in Children With Autism Spectrum Disorder - Operto, Francesca Felicia; Pastorino, Grazia Maria Giovanna; Scuoppo, Chiara; Padovano, Chiara; Vivenzio, Valentina; Pistola, Ilaria; Belfiore, Gilda; Rinaldi, Rosetta; de Simone, Valeria; Coppola, Giangennaro (Frontiers in Neuroscience, 2021)
Abstract Background: The aim of our study was to compare adaptive skills, emotional/behavioral problems, and parental stress among children with different severity levels of Autism Spectrum Disorder (ASD) symptoms. Methods: This study included a sample of 88 subjects with ASD (mean age = 6.00 ± 2.70).All subjects underwent standardized neuropsychological tests for the assessment of symptoms of the autism spectrum (Autism Diagnostic Observation Schedule-Second Edition), adaptive level (The Vineland Adaptive Behavior Scales, Survey Interview, 2nd edition), behavioral and emotional problems (Child Behavior CheckList CBCL) and parental stress (Parental Stress Index Short Form-PSI-SF). Non-parametric statistical methods (Kruskal-Wallis test and Mann-Whitney U test for post-hoc analysis) and linear regression analysis were used in this study. Results: Children who had higher severity levels of ASD symptoms had less adaptive functioning; younger children showed more severe symptoms of ASD; older children had better communication skills. The presence of greater adaptive difficulties was related to a greater presence of internalizing problems. An increase in parental stress levels was related to an higher severity of ASD symptoms, fewer adaptive skills, and a greater presence of internalizing and externalizing problems. Conclusion: This study suggests that the adaptive behavior should be considered in order to planning a habilitation intervention in children with autism. It is also important to monitor emotional/behavioral problems and parental stress levels in order to provide parenting support and improve the family quality of life.